Brief notes on the need to legitimizethe environmental impact assessment in mining The legacy of Tia Maria and Shahuindo - Palomino Seguín, Daniel Jesús (2016)
This article focuses on some of the most important constitutional and legal provisions that regulate the performing of mining activities in Peru, as a premise to analyze how the discussion about economic development and environmental protection has been misunderstood, and how it has become in one of the main causes of social conflicts in this sector. For this purpose, two remarkable and recent judgments enacted by the Mining Council of the Ministry of Energy and Mines of Peru will be reviewed in order to confirm the need to  redefine  the  role  of the Government on encouraging the private investment in this extractive activity.